Numerical Optimization of Internal Geometry for Additively Manufactured Hydraulic Manifolds - Bartolj, Jan; Schmitz, Katharina; Vukašinović, Nikola; Majdič, Franc (International Conference Fluid Power 2025: Conference Proceedings, 2025)
This study presents a novel approach for the design and optimisation of hydraulic manifolds with self-supporting geometries that are compatible with additive manufacturing. Conventional manifolds with a circular cross-section often require complex post-processing as the internal channels are not supported. In this work, configurations of cross-sectional shapes that do not require support structures are investigated. A parametric optimisation and an adjoint gradient algorithm strategy were implemented to refine the cross-sectional geometry of the internal channels with the aim of minimising pressure loss while ensuring manufacturability. Use of CFD simulations to analyse the flow behaviour and pressure losses for different design variants. The integration of self-supporting features not only improves flow efficiency but also realises the full potential of AM by reducing manufacturing time and post-processing requirements. This research contributes to the development of more efficient, production-ready hydraulic systems through simulation-based design methods that take cross-sectional geometry into account.